LITERATURE REVIEW FAKTOR RISIKO STRESS AKIBAT KERJA PADA SATUAN PENGAMANAN TAHUN 2020 - Evan Rhesa Sudarto; Liem Jen Fuk; Susanty Dewi Winata (Jurnal MedScientiae, 2022)
The security guard is one of the security forces on duty in an agency. The main task of a security guard is to carry out security and order in his workplace which includes aspects of physical security, personnel, information and other technical security. The profession as a security guard is inseparable from the stress caused by work. Work stress can occur when someone is required to work beyond their capacity. When a person cannot handle excessive workloads, he will experience stress. The purpose of this research is to see what are the risk factors for stress on security guard. All 9 data in this study is gathered using google scholar. Variables of this study is sample that researching occupational stress factor of Demand-Control (Job Strain) and Effort-Reward Imbalance. Study outcome showed that Demand-Control (Job Strain) and Effort-Reward Imbalance is the factor that stimulate stress and will be presented in a workplace.